2017
DOI: 10.1158/1538-7445.am2017-702
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 702: A novel cell-penetrating ATF5 antagonist peptide CP-d/n-ATF5 exerts in vitro and in vivo anti-tumor effects in a broad spectrum of pediatric cancers

Abstract: Purpose: Activating transcription factor 5 (ATF5), a member of the ATF/CREB family transcription factor, has been implicated in the pathogenesis of glioblastoma and other adult tumors. Recently, a novel cell penetrating (CP-d/n-ATF5) peptide has been developed to antagonize ATF5 function. The goal of the current study is to test the efficacy of CP-d/n-ATF5 in several children tumors including neuroblastoma, hepatoblastoma, Ewing sarcoma, and rhabdoid tumor, in vitro and in vivo. Methods: A panel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…This notion is supported by our current work revealing downregulation of ATF5 in PRMT1 knockdown cells regardless of MYCN amplification status, and similar sensitivity in MYCNnon-amplified neuroblastoma cells to PRMT1 inhibition as that in MYCN-amplified cells, as well as by initial studies of ATF5 in neuroblastoma 11 . Yamashiro's group found that suppression of ATF5 activity with an inhibitory peptide led to a concentration-dependent decrease of cell viability and increase of cell apoptosis in a panel of human neuroblastoma cell lines regardless of MYCN amplification 11 . Therefore, it is tempting to speculate that ATF5 may act as a general downstream effector of PRMT1mediated survival signaling in neuroblastoma.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This notion is supported by our current work revealing downregulation of ATF5 in PRMT1 knockdown cells regardless of MYCN amplification status, and similar sensitivity in MYCNnon-amplified neuroblastoma cells to PRMT1 inhibition as that in MYCN-amplified cells, as well as by initial studies of ATF5 in neuroblastoma 11 . Yamashiro's group found that suppression of ATF5 activity with an inhibitory peptide led to a concentration-dependent decrease of cell viability and increase of cell apoptosis in a panel of human neuroblastoma cell lines regardless of MYCN amplification 11 . Therefore, it is tempting to speculate that ATF5 may act as a general downstream effector of PRMT1mediated survival signaling in neuroblastoma.…”
Section: Discussionsupporting
confidence: 82%
“…Yamashiro's group identified ATF5 as a potential synthetic lethal gene to MYCN-amplified neuroblastoma 10 . Their initial studies demonstrate that ATF5 is highly expressed in MYCNamplified tumors, and that silencing of ATF5 inhibits cell proliferation and induces cell apoptosis 10,11 . They further show that an ATF5-targeting peptide has profound in vitro and in vivo cytotoxic and apoptotic effects on neuroblastoma 11 .…”
Section: Prmt1 Promotes Neuroblastoma Cell Survival Through Atf5mentioning
confidence: 99%